Concerns and professional development needs of university faculty in adopting online learning - Hwu, Shih-Hsung (Kansas State University, 2011)
The purpose of this mixed methods study was to explore concerns and professional development needs of faculty at the University Alaska Fairbanks (UAF) on the adoption of online learning (OL). This study was also in response to Title 24 of the Alaska Statute’s Recommendation #3, which required sufficient faculty training in distance education technologies for teaching UAF distance courses. This study utilized the Concerns Based Adoption Model (CBAM) as its theoretical framework. A mixed methods design was used to address the research questions. Both quantitative and qualitative methods were used to collect and analyze data. A non-experimental, cross-sectional survey design was used, incorporating the Stages of Concern Questionnaire (SoCQ). Quantitative measures included surveys were sent out to 253 UAF faculty. Ninety-six surveys were returned and usable, with a final response rate of 39%. MANOVA analyses were used to identify potential variables predictive of faculty member’s concerns and professional development needs regarding the implementation of OL. Qualitative measures included three open-ended questions and sixteen faculty interviews, chosen through stratified sampling. The Stages of Concern Questionnaire indicated that the majority of UAF faculty members displayed a typical SoCQ “nonuser” profile in adopting OL. Faculty’s highest concerns were unrelated, self, and task concerns, with a slight tailing-up of impact-refocusing concerns, indicating resistance to OL. Individual variables found to potentially be predictive of faculty members’ concerns included years of teaching experience, administrative support of technology and academic rank. Qualitative measures revealed that overall themes were administrative support, including workload consideration and tenure recognition. Professional development needs included current technology and LMS (Blackboard) workshops. At the same time, faculty voiced their concerns about OL through the themes of instructional quality and support (technical assistance and equipment) concerns. Several faculty members also stated that they needed no support and their resistance of OL. Recommendations for UAF included holistic approach to administrative support, proper recognition of achievements OL achievements, promotion of learner-centered methodology in the transition to OL, professional development that lead to a more collaborative community, an enhanced role for centralized support for staff engaged in OL and LMS training. Recommendations for future studies included further qualitative studies to elucidate faculty concerns within the University of Alaska system. A national study was recommended to help faculty and administrators create better university OL policies and discover mutual expectations of how teaching and developing OL courses could be viewed as part of a new approach to workload considerations in a changing university climate, including the tenure and promotion process.
Keywords: Online learning; SoCQ; Professional development; University; CBAM; Concerns; Continuing education (0651)